2023
DOI: 10.1097/ms9.0000000000001425
|View full text |Cite
|
Sign up to set email alerts
|

Clinical indications and outcomes of Impella devices for severe cardiogenic shock in COVID-19 patients: a systematic review

Bahadar S. Srichawla,
Vincent Kipkorir,
Manraj Sekhon

Abstract: Background: Coronavirus disease 2019 (COVID-19) can present with significant cardiac dysfunction, including cardiogenic shock. Mechanical circulatory support with an Impella device may be utilized in these patients to support and offload native right ventricle (RV) and left ventricle (LV) function. This systematic review aims to describe clinical indications, management, laboratory data, and outcomes in patients with severe cardiogenic shock from coronavirus disease 2019 (COVID-19) treated with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Considering its importance in cardiovascular disease, a population-based study showed that higher ACE2 plasma levels are associated with a greater risk of severe cardiovascular disease [20]. COVID-19 has been found to increase the risk of cardiogenic shock [21,22], cardiac arrhythmias [23,24], acute myocardial injury [25,26] and sometimes sudden death in patients with cardiovascular disease [15,27,28], and at the same time, patients with cardiovascular disease have a higher risk of mortality due to COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Considering its importance in cardiovascular disease, a population-based study showed that higher ACE2 plasma levels are associated with a greater risk of severe cardiovascular disease [20]. COVID-19 has been found to increase the risk of cardiogenic shock [21,22], cardiac arrhythmias [23,24], acute myocardial injury [25,26] and sometimes sudden death in patients with cardiovascular disease [15,27,28], and at the same time, patients with cardiovascular disease have a higher risk of mortality due to COVID-19.…”
Section: Introductionmentioning
confidence: 99%